Preparation and Activity of Some Novel Organo-metallic Complexes against Helicobacter pylori - Nagarajan, Ramaswamy; Mehtaa, Sureshchandra Ishwarlal; Naik, Suresh Ramnath; Fabry, Werner (Arzneimittelforschung, 1999)
Some novel organo-metallic complexes were prepared by complexing the antibiotics erythro- mycin (CAS 114-07-8), doxycycline (CAS 564-25-0), ciprofloxacin (CAS 85721-33-1) and amoxicillin (CAS 26787-78-0) with bismuth citrate and their antibacterial activity against Helicobacter pylori and other micro-organisms were investigated. Amoxicillin-bismuth citrate had the strongest activity against H. pylori with a lowest minimum inhibitory concentration of 0.007 mg/l. The complexes exhibited moderate activity against Staphylococcus aureus, Sta- phylococcus epidermidis, Enterococcus faecalis and Bacillus subtilis. The findings suggest that the activity of these organo-metallic complexes might be specifically directed against H. pylori.
Keywords: Antibiotics, complexing with bismuth citrate; in vitro activity; Bismuth citrate, complexing with antibiotics; Helicobacter pylori; Organo-metallic complexes